(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2024)
This study examines a Northern Italian Sigillata unpublished Sarius cup, decorated with grotesque figures, datable to the late Augustan age. This cup was found in 1890 near Bovolone (Verona) in a grave together with an Henkeldellenbecher and a Firmalampe. Among the few vases of Northern Italian Sigillata with grotesque figures, the same punches used in the cup from Bovolone appear in specimens found in Budrio (Bologna), Chiunsano (Rovigo), Aquileia, Vrhnika (Slovenia) and Velika Mrdakovica (Croatia). These almost skeletal figures, whose models are to be found in Hellenistic craftsmanship, are probably linked to comic performances; however, we don’t believe that there are any real scenes.